2022
DOI: 10.3390/microorganisms10020484
|View full text |Cite
|
Sign up to set email alerts
|

Cupriavidus metallidurans CH34 Possesses Aromatic Catabolic Versatility and Degrades Benzene in the Presence of Mercury and Cadmium

Abstract: Heavy metal co-contamination in crude oil-polluted environments may inhibit microbial bioremediation of hydrocarbons. The model heavy metal-resistant bacterium Cupriavidus metallidurans CH34 possesses cadmium and mercury resistance, as well as genes related to the catabolism of hazardous BTEX aromatic hydrocarbons. The aims of this study were to analyze the aromatic catabolic potential of C. metallidurans CH34 and to determine the functionality of the predicted benzene catabolic pathway and the influence of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Conversely, while these strains may be less efficient in VOC degrading, their reduced competitiveness left niches for the activities of non-degraders which in turn, may have improved the overall consortia performance, as reflected by high FS . Among the 7 non-degraders, Cupriavidus metallidurans and Rhodococcus Sp 3 seem to be the only two strains affecting the consortia behaviour and thus were very likely to directly participate in the VOCs degradation process due to their frequent presence in consortia of high GS and CI value and metabolic capability reported in other studies ( Cébron et al, 2008 ; Alviz-Gazitua et al, 2019 , 2022 ). Other non-degraders including Pseudomonas syringae , Agromyces atrinae , Ochrobactrum anthropic and two Plantibacter strains were seen as ‘weak’ bacteria members in the consortia with little effect on any of the parameters regardless of their presence or absence, nor the variation of their combinations.…”
Section: Resultsmentioning
confidence: 71%
“…Conversely, while these strains may be less efficient in VOC degrading, their reduced competitiveness left niches for the activities of non-degraders which in turn, may have improved the overall consortia performance, as reflected by high FS . Among the 7 non-degraders, Cupriavidus metallidurans and Rhodococcus Sp 3 seem to be the only two strains affecting the consortia behaviour and thus were very likely to directly participate in the VOCs degradation process due to their frequent presence in consortia of high GS and CI value and metabolic capability reported in other studies ( Cébron et al, 2008 ; Alviz-Gazitua et al, 2019 , 2022 ). Other non-degraders including Pseudomonas syringae , Agromyces atrinae , Ochrobactrum anthropic and two Plantibacter strains were seen as ‘weak’ bacteria members in the consortia with little effect on any of the parameters regardless of their presence or absence, nor the variation of their combinations.…”
Section: Resultsmentioning
confidence: 71%
“…Conversely, while these strains may be less e cient in VOC degrading, their reduced competitiveness left niches for the activities of non-degraders which in turn, may have improved the overall consortia performance, as re ected by high FS. Among the 7 non-degraders, Cupriavidus metallidurans and Rhodococcus Sp3 seem to be the only two strains affecting the consortia behaviour and thus were very likely to directly participate in the VOCs degradation process due to their frequent presence in consortia of high GS and CI value and metabolic capability reported in other studies (Cébron et al, 2008;Alviz-Gazitua et al, 2019, 2022a. Other non-degraders including Pseudomonas syringae, Agromyces atrinae, Ochrobactrum anthropic and two Plantibacter strains were seen as 'weak' bacteria members in the consortia with little effect on any of the parameters regardless of their presence or absence, nor the variation of their combinations.…”
Section: Combination Signi Cance and Single Strain Effect Testmentioning
confidence: 82%
“…However, it was at a lower abundance in most of the high Pb-toluene, indicating that it was not as competitive under those conditions as the other genera present and benzene samples co-contaminated with Cd or Pb when compared to the control samples. Several strains within this group have been isolated and found to degrade aromatic hydrocarbons (Alviz-Gazitua et al 2022 ; Morya and Salvachúa 2020 ; Witzig et al 2006 ). For example, Cupriavidus metallidurans st. CH34 has degraded benzene and toluene with Hg and Cd co-contamination (Alviz-Gazitua et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several strains within this group have been isolated and found to degrade aromatic hydrocarbons (Alviz-Gazitua et al 2022 ; Morya and Salvachúa 2020 ; Witzig et al 2006 ). For example, Cupriavidus metallidurans st. CH34 has degraded benzene and toluene with Hg and Cd co-contamination (Alviz-Gazitua et al 2022 ). In that study, the minimum inhibitory concentration of Cd was found to be 0.8 mM, which is greater than the concentrations we tested.…”
Section: Discussionmentioning
confidence: 99%